THE IMPORTANCE OF CASH FLOW IN THE FINANCIAL MANAGEMENT OF MICRO AND SMALL ENTERPRISES: A LITERATURE REVIEW - Campos, Camila Silva; Câmara, Larissa de Macedo; Costa, Leonardo Pastorin Vieira; Nascimento, Natália Talita Araújo (Seven Editora, 2026)
The research aims to analyze the importance of cash flow in the financial management of micro and small enterprises, based on a review of the scientific literature from 2020 to 2025. The following specific objectives are proposed: (1) to identify recommended practices for controlling and using cash flow in micro and small enterprises; (2) to survey the main benefits and challenges highlighted in recent literature regarding cash flow management; and (3) to analyze the relationship between the effective use of this tool and the financial sustainability of these organizations. The research problem is centered on answering the following question: what is the importance of cash flow for the financial management of micro and small enterprises in light of recent literature? Regarding the methodology, the study is qualitative in nature, with an exploratory-descriptive approach and based on a biblioFigureic review. Thirteen articles were selected through Google Scholar, using filters for the terms “cash flow,” “micro and small enterprises,” and “financial management.” The analysis was conducted through systematic summaries organized into three categories: recommended practices, benefits, and challenges of cash flow management. The results indicate that cash flow is a fundamental tool for financial control, decision-making, and short- and long-term planning. A lack of managerial training, informality, and the use of intuitive management methods were also identified. Although there is consensus on the importance of cash flow, a gap still exists between theoretical knowledge and its application in everyday practice.DOI: https://doi.org/10.56238/sevened2026.008-120